The German Real Estate Transfer Tax: Evidence for Single-Family Home Transactions - Carolin Fritzsche; Lars Vandrei (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
This paper uses recent data for single-family home purchases to study the effects of theGerman real estate transfer tax. We aim to separate the tax's short-term anticipatoryeffects from its long-term effects on real estate transactions. The data indicate that anincrease in the transfer tax is negatively correlated with the number of transactions thattake place in the market for single-family homes. We estimate that a one percentagepoint higher transfer tax produces enormous anticipation effects and yields approximately6% fewer transactions over the long run.
Keywords: H20; H71; R30; 330; Real estate transfer tax; housing markets; property taxation; anticipation effects